Freezing and Hydrate Formation in Aqueous Sodium Perchlorate Solutions. Issue 6 (14th March 2013) - Hennings, Erik; Heinz, Jacob; Schmidt, Horst; Voigt, Wolfgang
Abstract The determination of the phase diagram of the binary system sodium perchlorate – water is reported. Beside the eutectic point, two polymorph crystal structures of sodium perchlorate dihydrate were determined. The two crystal structures are discussed, compared to each other and to other known sodiumhalide dihydrate crystal structures. The two polymorphs of the perchlorate dihydrate represent the two variants of connected octahedra in the layer structure found for sodium halide dihydrates.